2018
DOI: 10.12659/msm.913885
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile Analysis of Circular RNAs in Ovarian Endometriosis by Microarray and Bioinformatics

Abstract: BackgroundEndometriosis is a common gynecologic disorder with enigmatic etiopathogenesis and is characterized by tumor-like biological behaviors. Recently, circular RNAs (circRNAs) have attracted considerable attention because they exert very important functions in the progression of human cancers. However, little is known about the functions and molecular mechanism of circRNAs in endometriosis.Material/MethodsA total of 20 patients with ovarian endometriosis and 4 normal endometrium from women free of endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…In this study, we investigated circRNA expression profiles in ecEM compared with euEM of endometriosis patients and identified 294 differentially expressed circRNAs, 146 upregulated and 148 downregulated. Most of those dysregulated circRNAs originate from exons or introns which are in accordance with previous researches (Shen et al, ; Xu et al, , ; Zhang, Ren, Xiao, Xia, & Fang, ). It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we investigated circRNA expression profiles in ecEM compared with euEM of endometriosis patients and identified 294 differentially expressed circRNAs, 146 upregulated and 148 downregulated. Most of those dysregulated circRNAs originate from exons or introns which are in accordance with previous researches (Shen et al, ; Xu et al, , ; Zhang, Ren, Xiao, Xia, & Fang, ). It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Xu et al () revealed for the first time the circRNA expression patterns between women with and without endometriosis and found that the increased level of circ_0004712 and circ_0002198 could help identify the patients with endometriosis. Zhang, Ren, et al () assessed the expression profiles of circRNAs in endometriosis by microarray analysis and detected 2,237 circRNAs differentially expressed among ectopic endometrium (EC) (endometriotic lesions), paired eutopic endometrium (EU), and normal endometrium from women free of endometriosis, and qRT‐PCR validation suggested that downregulated circ_103470 and circ_101102 matched the microarray results. In our study, four of nine upregulated circRNAs (hsa_circ_0003380, hsa_circ_0020093,hsa_circ_0008016 and hsa_circ_0077837) were confirmed by qRT‐PCR, which was consistent with sequence assays.…”
Section: Discussionmentioning
confidence: 95%
“…miR-200a was frequently overexpressed and is closely related to the migratory, proliferative, and invasive abilities of OC cells [80][81][82]. miR-141 was shown to be significantly upregulated in OC cell lines and advanced metastatic OC [83,84], and can inhibit GC apoptosis by targeting DAPK1 through the MAPK signaling pathway, leading to the development of polycystic ovary syndrome (PCOS) [85]. In this study, miR-200a and miR-141 expression were upregulated in the small follicles of uniparous goats, suggesting that these miRNAs might affect normal GC development, thereby affecting follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of clinical samples by microarray and bioinformatics methods revealed 88 differentially expressed circRNAs between eutopic and normal endometrium, of which 11 were up‐regulated and 77 were down‐regulated 12 . In addition, circ_103470 and circ_101102 were found to regulate epithelial‐mesenchymal transition (EMT) of endometriosis through sponge miR‐141‐5p 13 . Further functional analysis showed that downstream mRNAs of these differentially expressed circRNAs are mainly involved in immune‐inflammatory response and cell cycle regulation.…”
Section: Introductionmentioning
confidence: 99%